TRAINING ACCOUNTANTS AND AUDITORS: HOW TO HARMONIZE EDUCATIONAL PROGRAMS AND PROFESSIONAL STANDARDS - ROMAN Bulyga (Учёт. Анализ. Аудит, 2019)
The article focuses on the main tools and subjects which form a qualified employee and which call for the close cooperation between educational institutions, professional communities and employers. The author describes such new elements of the joint system to form the employee’s qualification as the bodies of independent qualification assessment (i. e. the Council on Professional Qualifications, Qualification Assessment Centers). The article also considers the peculiarities of the process of harmonization between educational programs and professional standards related to such types of activities as accounting and audit. Best practices are exemplified by theexperience of the Financial University under the Government of the Russian Federation in faculty representatives’ participating in the development of professional standards and further development of educational programs linked to professional standards.